Health literacy and its relationship with mental health and quality of life in freshmen students - Amirhossein Alinejad-Tilaki; Shabnam Omidvar; Farzan Kheirkhah; Afsaneh Bakhtiari; Hemmat Gholinia (BMC Public Health)
Abstract Introduction Health literacy is an effective indicator of people’s health level. Therefore, this study aimed to investigate health literacy and its relationship with mental health and quality of life in first-year medical sciences students. Methods and materials The cross-sectional study was conducted on freshmen- students of Babol University of Medical Sciences, Iran. 311 students were selected using a multi-stage sampling method. Data was collected by 4 questionnaires including demographic, health literacy questionnaire, General health questionnaire (GHQ-12), and quality of life (short form) (SF-12). Analysis of the data was done using SPSS version 22. Results The subjects were 45.5% female and 54.5% male. Almost 60% had adequate/excellent health literacy. A significant relationship between health literacy and the variables of gender and place of residence was found. The results indicated that health literacy, age, educational level, and residential place were predictors of students’ mental health. The regression test results showed that the variables of health literacy, age, educational program, and residential place were predictors of students’ mental health. The students’ mean score of quality of life was 68.81 ± 16.56. The regression test indicated that health literacy, educational level, and residential place were predictors of students’ quality of life. Conclusion This study emphasizes the central role of health literacy in shaping the mental health and quality of life of freshmen students.